Modifiable Source Code Virtual Views - Villavicencio, Gustavo (Companion Proceedings of the Brazilian Symposium on Software Engineering (SBES); 2019: Companion Proceedings of the 33th Brazilian Symposium on Software Engineering, 2020)
This paper introduces the modifiable source code virtual view concept, which is a variant of a source code fragment from the version used to generate the binary code for execution, enriched with information provided by the impact analysis process. A modifiable source code virtual view supports the maintenance process instead of the corresponding source code fragment used to generate the binary code, as is the current practice today. The set of key maintenance attributes (maintainability, reusability, etc.) are improved in the view, while the (opposite) set of key software execution attributes (performance, security, etc.) are improved in the source code fragment to generate the binary code. In between, there are refactoring transformations that adjust the metrics related to each set of key attributes, which also support the propagation of modifications from the view to its corresponding fragment in execution.